The Influence of Perceived Price and Customer Satisfaction on Customer Loyalty for Shopee E-Commerce Online Shopping - Airlangga Kusuma Agung; Hery Pudjoprastyono (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effect of Price Perception and Customer Satisfaction variables on Customer Loyalty for Shopee E-Commerce Shopping partially. This type of research is quantitative. The population in this study were Shopee consumers in Surabaya, aged 17-25 years who had made at least two purchases at Shopee e-commerce. The sample of this research is 78 respondents. The sampling technique used in this study was no change sample. Collecting data using a questionnaire as a source of primary research data. While the data processing technique used is Partial Least Square (PLS). Based on the results of the study it can be concluded that Price Perception has a significant positive effect on Customer Loyalty, Customer satisfaction has a positive effect on Customer Loyalty.